2022
DOI: 10.3389/fonc.2022.1002111
|View full text |Cite
|
Sign up to set email alerts
|

Practice of breast self-examination and associated factors among female health professionals working in public hospitals of Harari regional state: Eastern Ethiopia multicenter study

Abstract: Breast cancer is the most frequent malignancy among women in both developed and developing countries. Early detection of breast cancer using breast self-examination plays a substantial role in reducing its morbidity and mortality. Despite improved availability of health information the morbidity and mortality caused by breast cancer among females were increasing from time to time and there is no information regarding the practice of breast self-examination in our study area.ObjectiveThis study was aimed at ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Tese fndings are supported by recent studies from Dechasa et al [39], Shallo and Boru [40], Dagne et al [41], and Elias et al [42], who reported that the practice of BSE was signifcantly associated with having good knowledge about BSE practice among the respondents. Tose with good knowledge about BSE practice are more likely to perform BSE practice as compared to those who have poor knowledge, which explain that knowledge about the impact of breast cancer and having information on diagnostic methods for breast cancer enable them to perform BSE.…”
Section: Nursing Forummentioning
confidence: 56%
“…Tese fndings are supported by recent studies from Dechasa et al [39], Shallo and Boru [40], Dagne et al [41], and Elias et al [42], who reported that the practice of BSE was signifcantly associated with having good knowledge about BSE practice among the respondents. Tose with good knowledge about BSE practice are more likely to perform BSE practice as compared to those who have poor knowledge, which explain that knowledge about the impact of breast cancer and having information on diagnostic methods for breast cancer enable them to perform BSE.…”
Section: Nursing Forummentioning
confidence: 56%
“…17 Similar findings were reported by Dechasa et al in their study where they found 47.2% had ever performed BSE. 18 Only 23.36% of females performed BSE at the same time every month by using all needed techniques. As the current study was cross-sectional study, thus causal conclusions cannot be drawn.…”
Section: Practices Regarding Bsementioning
confidence: 99%